Java面向对象程序设计 - 梁胜彬 (清华大学出版社, 2023)
结合实用案例讲解Java语法、面向对象程序设计技术和核心API。 全书共10章，内容涵盖Java概述、Java语法基础、面向对象基础、面向对象高级技术、 Java API、异常处理机制、Java I/O流、多线程、Java GUI编程和Java网络编程等知识要点。案例丰富，以JDK 17和IntelliJ IDEA等流行的开发环境为依托，力求让读者通过案例 掌握Java编程技术。另一个特色是在阐释专业内容的同时自然融入思政元素， 具有鲜明的时代性和引领性。 可作为普通高等院校计算机、软件工程、人工智能等专业“面向对象程序设计”“Java程序设计”课程的教材，也适 合编程爱好者自学和培训使用。

Student engagement, higher education, and social justice: beyond neoliberalism and the market - Bramley, Corinna; Morrison, Keith (Routledge, 2023)
"Student engagement is a catch-all term, irresistible to educators and policy makers, and serving many agendas and purposes. This ground-breaking book provides a powerful theory of student engagement, rooted in critical theory and social justice. It sets out a compelling argument for student engagement to promote social justice and to repel neoliberalism in, and through, higher education, addressing three key questions: -Student engagement in what? -Student engagement for what? -Student engagement for whom? The answers draw on Habermas, Honneth, Gramsci, Foucault, and Giroux in examining ideology, power, recognition, resistance, and student engagement, with examples drawn from across the world. It sets out key features, limitations and failures of neoliberalism in higher education, and indicates how student engagement can resist it. Student engagement calls for higher education institutions to be sites for challenge, debate on values and power, action for social justice, and for students to engage in the struggle to resist neoliberalism, taking action to promote social justice, democracy, and the public good. This book is essential reading for educators, researchers, managers and students in higher education, social scientists and social theorists. It is a call to reawaken higher education for social justice, human rights, democracy and freedoms"–
Keywords: Active learning; Education; Higher; Neoliberalism; Social aspects; Social justice and education

Book of Proceedings of ARTeFACTo 2022 Macao, Third International Conference on Digital Creation in Arts, Media and Technology - Emerging Extended Realities - Estadieu, G; Martins de Abreu, F.; Caires, Carlos; Fernandes Marco, A. (IEEE, 2023)

(Un)directed Reading: Selected Students' Work Directed Reading 2020/21 University of Saint Joseph, Macao, China - Olga Ng Ka Man, Sandra (University of Saint Joseph, 2023)
Keywords: Literature

Computerized Systems for Diagnosis and Treatment of COVID-19 - Lobo Marques, Joao Alexandre; Fong, Simon James (Springer International Publishing, 2023)
Keywords: Artificial Intelligence; Biofeedback; Computerized Diagnostic Support; Covid-19; Signal and Image Processing

Memory and Identity: the proceedings of the 28th ASEACCU Annual Conference - Morgan, Stephen (USJ University Press, 2023)

Guide to Street Art in Macau. - Simões, Filipa (CURB Center for Architecture and Urbanism, 2023)

Jornalismo e Qualidade no Mundo de Expressão Portuguesa - Camponez, Carlos; Simões, José Manuel; Christofoletti, Rogério (University of Saint Joseph, 2022)
"Jornalismo e Qualidade no Mundo de Expressão Portuguesa"propõe uma análise sobre a paisagem do jornalismo nos oitopaíses de língua oficial portuguesa - Portugal, Angola, Brasil, Cabo Verde, Moçambique, Guiné-Bissau, São Tomé e Príncipee Timor-Leste - e na Região Autónoma Especial de Macau. Olivro é uma reflexão sobre a legislação, o plano jurídico-constitucionalque enquadra os media no espaço lusófono, os contextosde mercado, as especificidades inscritas em fatoreshistóricos e económicos, em percursos políticos, bem comosobre as relações entre os media e os jornalistas e estes e opoder regulador do Estado.Os trabalhos reunidos nesta obra escrita por autores que partilhamentre si um dos idiomas mais falados do planeta, mostram as diferentes realidades do jornalismo no espaço dalíngua portuguesa, nomeadamente as suas redes de conhecimento, de empenho na promoção da qualidade da informação, de intercompreensão entre povos e culturas, de novas einovadoras formas de parcerias sociais com vista à partilha e àconstrução de mundividências.

Interaction design for a contemporary learning and teaching environment: promoting independent learning at the primary level - Chan, Ka Chi (University of Saint Joseph, 2022)
The world is perpetually changing, and the COVID-19 pandemic has taught us that the future is full of unforeseen challenges and potentialities. What are the implications of the advancement in technology on education? How are teachers coping with contemporary educational expectations? Is there a need to redesign the learning environment? What is the exact nature of the forces driving such a change? Is there anything we can learn from successful innovations around the globe? The goals of this dissertation include designing a learning/teaching app and redesigning classroom furniture for primary-level education. A design thinking methodology is used, working through the phases of empathizing, defining, ideating, prototyping and testing the two potential designs
Keywords: Design; Interaction analysis in education; Interactive multimedia

Epidemic analytics for decision supports in COVID19 crisis - Lobo Marques, Joao Alexandre; Fong, Simon (Springer, 2022)
Covid-19 has hit the world unprepared, as the deadliest pandemic of the century. Governments and authorities, as leaders and decision makers fighting against the virus, enormously tap on the power of AI and its data analytics models for urgent decision supports at the greatest efforts, ever seen from human history. This book showcases a collection of important data analytics models that were used during the epidemic, and discusses and compares their efficacy and limitations. Readers who from both healthcare industries and academia can gain unique insights on how data analytics models were designed and applied on epidemic data. Taking Covid-19 as a case study, readers especially those who are working in similar fields, would be better prepared in case a new wave of virus epidemic may arise again in the near future.

Classical theism and Buddhism: connecting metaphysical and ethical systems - McNabb, Tyler Dalton; Baldwin, Erik Daniel (Bloomsbury Academic, 2022)
"As an atheistic religious tradition, Buddhism conventionally stands in opposition to Christianity, and any bridge between them is considered to be riddled with contradictory beliefs on God the creator, salvific power and the afterlife. But what if a Buddhist could also be a Classical Theist? Showing how the various contradictions are not as fundamental as commonly thought, Tyler Dalton McNabb and Erik Baldwin challenge existing assumptions and argue that Classical Theism is, in fact, compatible with Buddhism. They draw parallels between the metaphysical doctrines of both traditions, synthesize their ethical and soteriological commitments and demonstrate that the Theist can interpret the Buddhist's religious experiences, specifically those of emptiness, as veridical, without denying any core doctrine of Classical Theism. By establishing that a synthesis of the two traditions is plausible, this book provides a bold, fresh perspective on the philosophy of religion and reinvigorates philosophical debates between Buddhism and Christianity"–
Keywords: Buddhism; Comparative studies; Relations Theism; Theism

Replication research in education: a guide to designing, conducting and analysing studies - Morrison, Keith (Routledge, 2022)
"Providing an overview of key issues in theory and practice, Replication Research in Education is designed to identify and discuss the benefits and challenges facing replication studies in education. Both clear and practical, this ground-breaking volume covers how to introduce, develop, conduct, report and discuss these studies, and the issues they raise for policy and practice. Bridging theory and practice, this book considers what replication research should look like, how it should be conducted and how to judge when it has been successful. It enables researchers to plan and conduct studies successfully, from their earliest stages through to completion. This key text: brings together in a single volume, existing issues, claims and counter-claims, discourses and practices of replication introduces, covers, and extends this field of research, indicating its possibilities and limits expands and adds to existing discussions and practices will enable researchers to design, conduct, evaluate and critique studies. The comprehensive and exhaustive coverage of issues and practices within Replication Research in Education make it a "must read" for all novice and experienced educational researchers who are considering, conducting, and reviewing replication studies in education"–

Succession in Chinese family business: transgenerational transmission of social capital in Macao - Phillips, Jenny O. L. (University of Saint Joseph, 2022)
Macao is well known for its gaming industry. However, there are also many traditional small-to-medium enterprises which are family-owned and run. There is no doubt that social capital is one of the key competitive advantages that family businesses possess, particularly when it comes to Chinese businesses with strong family values that emphasize the importance of trustworthiness and guanxi (relationships). As opposed to other forms of capital, social capital cannot be passed from one generation to another through the will of the incumbents. So, how is social capital passed on in family businesses from one generation to the next? Based on an in-depth study of five cases of successful family businesses in Macao, this research identified the forms of social capital present in business families and the succession process of these firms. From the generalizations drawn from the five cases, a theoretical framework is proposed to understand the intergenerational transmission of social capital in Chinese family businesses
Keywords: China Macau (Special Administrative Region); Family-owned business enterprises

《學會閱讀》叢書第一輯 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

《學會閱讀》叢書第二輯 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文兒歌集 – 果子級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文學習卡 – 果子級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文學習卡 – 花兒級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文學習卡 – 葉芽級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

Book of Proceedings of ARTECH 2021 - 10th International Conference on Digital and Interactive Arts (Hybrid Praxis – Art, Sustainability & Technology) - Lopes, Maria Manuela; Lopes, Paulo Bernardino; Araújo, António; Olivero, Lucas Fabian; Marcos, Adérito Fernandes (2021)

The Role of Metaxy in the Political Philosophy of Eric Voegelin - Duraj, Jarosław (Peter Lang, 2021)
This book is a study of Eric Voegelin (1901-1985) and of the role played by metaxy in his vision of political philosophy. Metaxy, already defined by ...

The Role of Metaxy in the Political Philosophy of Eric Voegelin - Duraj, Jarosław (Peter Lang US, 2021)
This book is a study of Eric Voegelin (1901-1985) and of the role played by metaxy in his vision of political philosophy. Metaxy, already defined by Plato as the "in-between" matrix of the human condition, is for Voegelin a powerful notion that symbolizes the intermediate state in which man experiences diverse and opposing tensions such as the ones between immanence and transcendence or mortality and immortality. The metaxy constitutes the realm of the divine-human mutual participation (methexis), and its locus resides in human consciousness (nous), there where the divine reality manifests itself as the origin of being. Being the field of intermediation between opposing forces, man has to keep the balance of consciousness in order to differentiate the noetic and pneumatic dimensions and so attune his life to the divine ground of being. This book claims that for Voegelin metaxy shapes the possibility of the philosophical, historical, political and religious orientation in life. Indeed, Voegelin’s approach deserves recognition as an option adequate for addressing the intellectual challenges engendered by modern and postmodern philosophies.

Bioethics : ethics of life - Gomez, Fausto B. (University of Saint Tomas Publishing House, 2021)

A cognitive semantic study of biblical Hebrew: the root šlm for completeness-balance - Leong, Andrew Chin Hei (Brill, 2021)
"Semantic studies of the Biblical Hebrew verb "whole" have been influenced by those of its most invoked nominal form "whole". In this volume Andrew Chin Hei Leong shows that the concepts of balance, alliance, and completeness form the basic semantic structure of "whole". Previous studies on "whole" employed either historical or textual methodology, which has been dominant in biblical lexical studies. In addition to these methods, in Leong develops a systematic semantic methodology from Cognitive Semantics and Frame Semantics, to demonstrate that it is balance, rather than completeness, that is the most central concept in holding the semantic network together"–
Keywords: Bible; Hebrew language; Language; style; Semantics; Shlm (The Hebrew root)

Predictive Models for Decision Support in the COVID-19 Crisis - Marques, João Alexandre Lobo; Gois, Francisco Nauber Bernardo; Xavier-Neto, Jose; Fong, Simon James (Springer International Publishing, 2021)
COVID-19 has hit the world unprepared, as the deadliest pandemic of the century. Governments and authorities, as leaders and decision makers fighting the virus, enormously tap into the power of artificial intelligence and its predictive models for urgent decision support. This book showcases a collection of important predictive models that used during the pandemic, and discusses and compares their efficacy and limitations. Readers from both healthcare industries and academia can gain unique insights on how predictive models were designed and applied on epidemic data. Taking COVID19 as a case study and showcasing the lessons learnt, this book will enable readers to be better prepared in the event of virus epidemics or pandemics in the future.

John Henry Newman and the development of doctrine: encountering change, looking for continuity - Morgan, Stephen (The Catholic University of America Press, 2021)
"In focusing on the gestation of "An Essay on the Development of Christian Doctrine" (1845), John Henry Newman's last work as an Anglican and presaging his transition to Catholicism, this book examines how Newman accounted for doctrinal continuity in the face of evidence of change in the history of the church"–

Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular - Morgan, Stephen (USJ Press, 2021)

Taming randomized controlled trials in education: exploring key claims, issues and debates - Morrison, Keith (Routledge, Taylor & Francis Group, 2021)
"There is a recent surge in the use of randomized controlled trials (RCTs) within education globally, with disproportionate claims being made about what they show, 'what works', and what constitutes the best 'evidence'. Drawing on up-to-date scholarship from across the world, Taming Randomized Controlled Trials in Education critically addresses the increased use of RCTs in education, exploring their benefits, limits and cautions, and ultimately questioning the prominence given to them. While acknowledging that randomized controlled trials do have some place in education, the book nevertheless argues that this place should be limited. Drawing together all arguments for and against RCTs in a comprehensive and easily accessible single volume, the book also adds new perspectives and insights to the conversation; crucially, the book considers the limits of their usefulness and applicability in education, raising a range of largely unexplored concerns about their use. Chapters include discussions on: The impact of complexity theory and chaos theory Design issues and sampling in randomized controlled trials Learning from clinical trials Data analysis in randomized controlled trials Reporting, evaluating and generalizing from randomized controlled trials. Considering key issues in understanding and interrogating research evidence, this book is ideal reading for all students on Research Methods modules, as well as those interested in undertaking and reviewing research in the field of education"–
Keywords: Clinical trials; Education; Educational indicators; Research Data processing; Research Methodolgy

Retrieving the Sense of the Sacred: a Paradigm of Silence in the Liturgy - Wong, Lee Chun (University of Saint Joseph, 2021)
Keywords: Catholic Church; Liturgy Theology; Religious aspects Catholic Church; Silence

Pilgrimage Christian and Secular: a Phenomenological Approach - Yuan, Haojun (University of Saint Joseph, 2021)
In the light of the many kinds of journeys that have been considered pilgrimages, this book uses phenomenology as a method to examine the claim that pilgrimage is a journey to the ‘center’ during which pilgrims seek meaning s for themselves. First, by analyzing a phenomenology of Christian pilgrimage, this work attempts to identify what commonalities, as well as differences, exist between Christian pilgrimage and secular pilgrimage in terms of ‘natural attitude’. Next, by using a phenomenological method, such as transcendental reduction, the distinction between these two types of pilgrimage could be clarified that the happiness sought in Christian pilgrimage is both intentionally spiritual and sustainable, while primarily intellectual or sensory in secular pilgrimage. Lastly, this work seeks to establish whether or not ‘being at leisure’ is the primary element for pilgrims whose aim is to attain an understanding of happiness during a pilgrimage
Keywords: Christian pilgrims and pilgrimages; Phenomenology

Macao’s mangroves - Tagulao, Karen; Chan, Sek Kiu (University of Saint Joseph, 2020)